Pan-cancer analysis identifies NT5E as a novel prognostic biomarker on cancer-associated fibroblasts associated with unique tumor microenvironment - Xue, Xin-miao; Liu, Yu-yang; Chen, Xue-min; Tao, Bing-yan; Liu, Peng; Zhou, Han-wen; Zhang, Chi; Wang, Li; Jiang, Yu-ke; Ding, Zhi-wei; Shen, Wei-dong; Zhang, Jun; et al. (Frontiers in Pharmacology, 2022)
Background: Ecto-5′-nucleotidase (NT5E) encodes the cluster of differentiation 73 (CD73), whose overexpression contributes to the formation of immunosuppressive tumor microenvironment and is related to exacerbated prognosis, increased risk of metastasis and resistance to immunotherapy of various tumors. However, the prognostic signiﬁcance of NT5E in pan-cancer is obscure so far. Methods: We explored the expression level of NT5E in cancers and adjacent tissues and revealed the relationship between the NT5E expression level and clinical outcomes in pan-cancer by utilizing the UCSC Xena database. Then, correlation analyses were performed to evaluate the relationship between NT5E expression and immune infiltration level via EPIC, MCP-counter and CIBERSORT methods, and the enrichment analysis were employed to identify NT5E-interacting molecules and functional pathways. Furthermore, we conducted single-cell analysis to explore the potential role of NT5E on single-cell level based on the CancerSEA database. Meanwhile, gene set enrichment analysis (GSEA) in single-cell level was also conducted in TISCH database and single-cell signature explorer was utilized to evaluate the epithelial-mesenchymal transition (EMT) level in each cell type. Results: The expression level of NT5E was aberrant in almost all cancer types, and was correlated with worse prognosis in nine cancers. Notably, NT5E overexpression was related to worse overall survival (OS) in pancreatic adenocarcinoma (PAAD), head and neck squamous cell carcinoma (HNSC), mesothelioma (MESO), stomach adenocarcinoma (STAD), uveal melanoma (UVM), cervical squamous cell carcinoma, and endocervical adenocarcinoma (CESC) (p<0.01). NT5E-related immune microenvironment analysis revealed that NT5E is associated positively with the degree of inﬁltration of cancer-associated fibroblasts (CAFs) and endothelial cells in most cancers. Enrichment analysis of cellular component (CC) demonstrated the critical part of NT5E played in cell-substrate junction, cell-substrate adherens junction, focal adhesion and external side of plasma membrane. Finally, single-cell analysis of NT5E illuminated that EMT function of CAFs was elevated in as basal cell carcinoma (BCC), skin cutaneous melanoma (SKCM), HNSC and PAAD. Conclusions: NT5E could serve as a potential prognostic biomarker for cancers. The potential mechanism may be related to the upregulated EMT function of CAFs, which provides novel inspiration for immunotherapy by targeting CAFs with high NT5E expression.